Plasma levels of matrix metalloproteinase-2 and -9 in male and female patients with cirrhosis of different aetiologies. Issue 11 (5th August 2015) - Huang, Chih-Yang; Tseng, Kuo-Chih; Lin, Ming-Nan; Tsai, Jen-Pi; Su, Cheng-Chuan
Abstract : Background: Liver fibrosis and cirrhosis may be reversible in some circumstances. Reliable diagnostic tests are necessary for monitoring hepatic fibrogenesis. Matrix metalloproteinase (MMP)-2 and MMP-9 are two of the major MMPs in the circulation and may be most relevant to hepatic fibrosis. The behaviour of MMPs may be significantly different in men and women and may also differ in cases of cirrhosis of various aetiologies. Aims: To evaluate the manifestations of MMP-2 and MMP-9 in liver cirrhosis of different aetiologies in men and women and to compare these patterns with those of healthy controls. Methods: We measured MMP-2 and MMP-9 levels in plasma samples from 112 patients with cirrhosis and 112 age- and gender-matched healthy controls. We then correlated these MMP levels with gender and disease aetiology. Results: Plasma MMP-2 concentrations in patients showed a trend towards increasing values with cirrhosis severity and were markedly increased in patients regardless of gender and aetiology compared with healthy controls (p<0.0001). Plasma mean MMP-9 levels were comparable in patients with cirrhosis and controls, but increased with disease severity. They were significantly lower in patients (130.5 ng/mL), female patients (85.4 ng/mL) and male patients (150.4 ng/mL) with mild cirrhosis than in controls (163.2 ng/mL), female controls (162.5 ng/mL) and male controls (163.3 ng/mL) (p=0.001, 0.041 and 0.009, respectively). MMP-2 and MMP-9 concentrations were not significantly different between genders among controls and among various patient subgroups. Conclusions: Plasma MMP-2 level may be a useful diagnostic marker for monitoring hepatic fibrogenesis in patients with disease of different aetiologies.